Frontline governmental cooperation in environmental governance: A case analysis on the ecological demonstration zone in China - Li, Li; Wang, Jiong; Huangfu, Xin; Lu, Yichao (Frontiers in Environmental Science, 2023)
Abstract: This study examines the construction of the Yangtze River Delta Eco-Green Integrated Development Demonstration Zone (Ecological Demonstration Zone). During the inspection and acceptance process of the higher-level government, the authors found two distinct types of government interactions between frontline environmental policy implementers and middle-level government and the public. The new interaction emphasizes cooperation between implementers and the public, whereas the traditional interaction involves collaboration between implementers and the government. This study seeks to understand the reasons behind the shift in frontline government interaction targets in environmental governance. The study uses fuzzy-set qualitative comparative analysis to explore the cooperation dynamics in the implementation of environmental policies and to uncover that the power to promote the interaction of frontline governments in environmental governance comes from institutional change factors such as fuzzy task models and qualitative on-site inspections and acceptances by higher-level governments.